1983
DOI: 10.1111/j.1600-051x.1983.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Blastogenic responsiveness of peripheral blood mononuclear cells from individuals with various forms of periodontitis and effects of treatment

Abstract: Experiments were done to learn whether or not the blastogenic responsiveness of peripheral blood mononuclear cells (PBM) from 34 patients to mitogens and homogenates of a panel of periodontal bacteria differs significantly from that of cells from 16 normal individuals. Groups of control individuals and patients with juvenile (JP), rapidly progressive (RP) and adult periodontitis (AP) were formed. Blastogenic responsiveness was assessed after 72 and 120 h incubation by measuring the uptake of radioactive precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
6
24
0
Order By: Relevance
“…These alterations may affect local lymphocyte proliferation and function, and may contribute to increased susceptibility to disease in certain individuals. Many authors have reported that lymphoblastic responses are induced by bacterial antigens in patients with gingivitis and periodontitis (3,9,10,12,14,19,21,28). In our present studies, we found that A. actinomycetemcomitans produced a proteinaceous ISTF.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These alterations may affect local lymphocyte proliferation and function, and may contribute to increased susceptibility to disease in certain individuals. Many authors have reported that lymphoblastic responses are induced by bacterial antigens in patients with gingivitis and periodontitis (3,9,10,12,14,19,21,28). In our present studies, we found that A. actinomycetemcomitans produced a proteinaceous ISTF.…”
Section: Discussionsupporting
confidence: 71%
“…Although the pathogenic mechanism of periodontal disease is not well known, it is generally accepted that the immune system plays an important role in bacterial infection and destruction of the periodontal tissues. Human periodontitis lesions are histologically characterized by a dense infiltrate of lymphocytes (19,20). The role of lymphocytes in these lesions is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with healthy controls, the spontaneous lymphocyte response (SLR, a measure of the AMLR) of peripheral blood lymphocytes is generally depressed in patients with early-onset and chronic forms of periodontitis (Osterberg et al, 1983;Tew et al, 1983;Suzuki et al, 1984;Boyatzis and Seymour, 1986;Amer et al, 1990) Differences between healthy and diseased subjects, however, have not always been found (Suzuki et al, 1984;Okada, 1991;Kimura et al, 1991). The cause for AMLR depression is not known, although adult periodontitis patients with depressed AMLR have fewer CD4+ CD45RA+ (nafve) T-cells and depressed interleukin-2 (IL-2) production when compared with patients with normal AMLR (Kimura et al, 1991;Okada, 1991).…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 99%
“…To explore whether this bias of the monocytes from periodontitis patients is derived from the chronic periodontal inflammation, periodontal treatment studies should shed light on this issue. Previous studies showed that following non-surgical periodontal therapy, the depressed autologous mixed lymphocyte response returned to normal limits in periodontitis patients (61,67). The Th2promoting phenotype of the monocytes from periodontitis patients, as evaluated in LPS-stimulated WBCC, also reversed after extensive non-surgical periodontal therapy including the use of systemic antibiotics (68).…”
Section: Monocyte Response After Periodontal Therapymentioning
confidence: 96%